A new synthetic output tracking scheme for non-minimum phase affine nonlinear systems. Issue 18 (December 2020) - Foghahaayee, Hoda N.; Menhaj, Mohammad B.; Talebi, Heidar A.
Abstract: This paper presents a nonlinear output tracking controller for non-minimum phase affine nonlinear systems. A new analytical method is given to find a proper synthetic output which makes the system minimum phase under a condition of static equivalence. This method is fully derived based on the closed form solution of the Hamilton-Jacobi-Bellman (HJB) equation associated with the cheap control problem. The new methodology employs an algebraic equation for any system with scalar internal dynamics and a differential equation for those with an internal dynamics of higher order. Furthermore, a numerical simulation is carried out to show how the results of the experiment are consistent with those of the theoretical analysis.